Structural biology of proteins involved in the replication of herpesviruses - Hew, Kelly Kai Li (2015)
Production of new infectious herpesvirus particles is dependent on the disruptions of host immune responses, herpesvirus DNA replication, assembly and reactivation from latency. To better understand herpesvirus replication, crystallographic and interaction studies were performed on several key proteins. This includes Kaposi’s sarcoma associated herpesvirus (KSHV) viral interferon regulatory factor 1 (vIRF-1), varicella zoster virus encoded thymidylate synthase (TS), tegument protein VP22 from herpes simplex virus 1 and KSHV-encoded ORF49. The structural and biophysical analyzes of the proteins provided structural and mechanistic insights and revealed multiple novel interactions with previously unknown partners. The VP22 structure established a previously unknown structural homology with another tegument protein ORF52. The complex structures of TS and vIRF-1 illustrated similar molecular details in substrate binding as their human counterparts. The work therefore contributes to a more comprehensive understanding of herpesvirus replication, reinforcing the importance of structural studies to understand molecular aspects of herpesvirus function.